Long-term surgical outcomes of gastric neuroendocrine carcinoma and mixed neuroendocrine-non-neuroendocrine neoplasms - Iwasaki, Kenichi; Barroga, Edward; Enomoto, Masaya; Tsurui, Kazushige; Shimoda, Yota; Matsumoto, Moe; Miyoshi, Kenta; Ota, Yoshihiro; Matsubayashi, Jun; Nagakawa, Yuichi (World Journal of Surgical Oncology, 2022)
Neuroendocrine carcinoma (NEC) and mixed neuroendocrine-non-neuroendocrine neoplasm (MiNEN) are extremely rare subtypes of gastric cancer. MiNEN is a mix of carcinomatous components and neuroendocrine neoplasm in the same lesion. NEC and MiNEN have a poor prognosis, are difficult to diagnose, and have no established treatment. Herein, we assessed the clinicopathological characteristics and long-term surgical outcomes of gastric NEC and MiNEN patients in our hospital. We retrospectively assessed 1538 patients pathologically diagnosed with gastric cancer and who underwent curative surgical resection at our institution between January 1999 and October 2021. Of these patients, 25 (1.6%) were pathologically diagnosed with neuroendocrine neoplasms. From these 25 patients, we retrospectively analyzed the clinicopathological characteristics and surgical outcomes of 13 (0.8%) patients pathologically diagnosed with NEC or MiNEN. The NEC and MiNEN patients consisted of 11 men and 2 women [mean age, 74 (62-84) years]. The preoperative histological diagnoses were NEC (n = 4) and adenocarcinoma (n = 9). The final pathological diagnoses were large cell neuroendocrine carcinoma (LCNEC; n = 7) and MiNEN (n = 6). Total gastrectomy was the most common surgical procedure (9/13, 69.2%), followed by distal gastrectomy (3/13, 23.1%) and proximal gastrectomy (1/13, 7.7%). Immunohistochemical staining showed 8 CD56-positive patients. All 13 patients were positive for chromogranin A and synaptophysin. The mean Ki-67 value was 64.8 (0-95)%, and the mean mitotic score was 107.9 (0-400). Nine patients survived without recurrence postresection. The median postresection overall survival time was 68.7 (8.0-129) months. The 5-year survival rate was 0.75 ([95% CI] 0.408-0.912). The surgical treatment outcomes of NEC and MiNEN patients were relatively favorable. Although evidence concerning the effectiveness of surgery alone is meager, radical resection as part of multidisciplinary treatment including chemotherapy can potentially improve prognosis.